Learners’ voice on ePortfolio as a learning tool in a Technical University: a case study / Linda Khoo Mei Sui … [et al.] - Khoo Mei Sui, Linda; Chai Sing, Hoo; Balakrishnan, Subatira; Subramaniam, Indra Devi; Fam, Soo-Fen (Akademi Pengajian Bahasa, 2021)
The importance of graduate attributes has been discussed over recent years as they are crucial for the students to equip these skills at the workplace. Graduates require the hard skills and the graduate attributes. This study investigates the impact of an ePortfolio as a tool in a subject to improve the Information Technology learners’ graduate attributes in communication, critical thinking and problem solving as well as teamwork. The objective of the study is to investigate the students’ voices on ePortfolio as a learning tool in a subject. An interview was carried out with 13 students to get the data at the end of the course. The results revealed that most of the learners agreed that ePortfolio had aided them to enhance their learning especially in communication, critical thinking and problem solving and teamwork skills. This proves that ePortfolio can be used as a device to improve students’ graduate attributes in their learning.